Beta 2 adrenergic receptor gene restriction fragment length polymorphism and bronchial asthma. - Ohe, M. (1995)
BACKGROUND--Beta 2 adrenergic dysfunction may be one of the underlying mechanisms responsible for atopy and bronchial asthma. The gene encoding the human beta 2 adrenergic receptor (beta 2ADR) has recently been isolated and sequenced. In addition, a two allele polymorphism of this receptor gene has been identified in white people. A study was carried out to determine whether this polymorphism is functionally important and has any relation to airways responsiveness, atopy, or asthma. METHODS--The subjects studied were 58 family members of four patients with atopic asthma. Restriction fragment length polymorphism (RFLP) with Ban-I digestion of the beta 2ADR gene was detected by a specific DNA probe with Southern blot analysis. Airways responses to inhaled methacholine and the beta 2 agonist salbutamol, the skin prick test, and serum IgE levels were also examined and correlated to the beta 2ADR gene RFLP. In addition, measurements of cAMP responses to isoproterenol in peripheral mononuclear cells were performed in 22 healthy subjects whose genotype for beta 2ADR was known. RESULTS--A two allele polymorphism (2.3 kb and 2.1 kb) of the beta 2ADR gene was detected in the Japanese population. Family members without allele 2.3 kb (homozygote of allele 2.1 kb) had lower airways responses to inhaled salbutamol than those with allele 2.3 kb. The incidence of asthma was higher in those without allele 2.3 kb than in those with allele 2.3 kb. The beta 2ADR gene RFLP had no relation to airways responses to methacholine and atopic status. cAMP responses in peripheral mononuclear cells of the subjects without allele 2.3 kb tended to be lower than those of the subjects with allele 2.3 kb. CONCLUSIONS--These results suggest that Ban-I RFLP of the beta 2ADR gene may have some association with the airways responses to beta 2 agonists and the incidence of bronchial asthma.